Optimization of Design Procedure for Column-base Connections according to EN 1993-1-8:2006 - Vu, Quoc Anh; Chu, Thi Hoang Anh; Pham, Ngoc Hieu (Periodica Polytechnica Civil Engineering, 2022)
The stiffness and the strength of a column-base connection have significant impacts on the behavior of a steel frame. The paper develops an interaction curve between moment and axial force for the column-base connections according to EN 1993-1-8:2006 with the variation of the base plate thickness and the bolt diameter. This is the fundamental base to determine the ultimate strength of a column-base plate that allows the designers to estimate the strength of column-base connections. This research investigates the relationship between the base plate thickness, the bolt diameter, and the moment strength of the column-base plate with a specific axial force to select an optimum solution. Also, the initial rotational stiffness is determined under a specific axial load and varied moments that satisfy the ultimate limit state. The relationship between moment–rotation is subsequently performed with the variation of the base plate thickness or the bolt diameter. The design procedure is proposed based on moment-axial force interaction curves and moment-rotation curves. This allows for optimizing the column-base connection from proper selections of base plate dimensions and bolt diameters.